Analysis of Factors Affecting Earnings Management Moderated by Institutional Ownership - Wirianata, Henny (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2020)
The objective of this research is to examine the empirical evidence of leverage, profitability, growth, and institutional ownership on earnings management in manufacturing companies listed in Indonesia Stock Exchange. This research used 54 listed manufacturing companies in Indonesia Stock Exchange, selected using a purposive sampling method, during the research period 2016 until 2018. Data were analyzed using multiple regression analysis. The result of the research indicates that leverage proxied by DAR has a negative significant influence on earnings management. Size and growth have a positive significant influence on earnings management. Profitability proxied by ROA and institutional ownership has no significant influence on earnings management. The results also show that institutional ownership could moderate but not significant the influence of leverage, profitability, and growth towards earnings management of manufacturing companies listed in Indonesia Stock Exchange period 2016-2018.